Human Trafficking Berkedok Teacher Exchange: Perspektif Perlindungan Guru dalam Hukum Internasional - Nugraheni, Nadea Lathifah; Pratama, Praditya Arcy (PGRI Kota Semarang, 2025)
This study examines the international legal response to the phenomenon of human trafficking disguised as internship programs. With the rise in human trafficking cases worldwide, particularly targeting young and vulnerable workers, it is crucial to understand how the international legal framework attempts to address this issue. This study analyzes various existing legal instruments, including the Palermo Protocol and the ILO Convention on Migrant Workers, and their implementation at the national level. Furthermore, the article explores the challenges faced in law enforcement and protecting the human rights of victims. Through case studies and recent data, the article offers recommendations for strengthening international cooperation and raising public awareness of the issue of human trafficking disguised as internships.